2010
DOI: 10.1111/j.1528-1167.2009.02278.x
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation might have a unique effect in reflex eating seizures

Abstract: SUMMARYWe studied the effects of vagus nerve stimulation (VNS) on eating seizures, which theoretically would be triggered by neural activity and signaling from organs innervated by the vagus nerve. Three adult patients with daily nonreflex and reflex eating seizures were studied; one patient also had hot-water seizures. One patient had bilateral polymicrogyria and two had normal magnetic resonance imaging (MRI) findings. All patients were submitted to VNS implantation and had at least 2 years of postimplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 10 publications
1
20
0
3
Order By: Relevance
“…Bunun dışında farklı tedavi seçenekleri uygulayan çalışmalar da olmuştur. [8] Örne-ğin, Cukiert ve ark. [8] bu olgularda vagal sinir stimülasyonu uygulamışlar ve olgularında %70-95 oranında nöbet kontrolü sağladıklarını bildirmişlerdir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Bunun dışında farklı tedavi seçenekleri uygulayan çalışmalar da olmuştur. [8] Örne-ğin, Cukiert ve ark. [8] bu olgularda vagal sinir stimülasyonu uygulamışlar ve olgularında %70-95 oranında nöbet kontrolü sağladıklarını bildirmişlerdir.…”
Section: Discussionunclassified
“…[8] Örne-ğin, Cukiert ve ark. [8] bu olgularda vagal sinir stimülasyonu uygulamışlar ve olgularında %70-95 oranında nöbet kontrolü sağladıklarını bildirmişlerdir. Yiyeceğin içeriğine göre tetiklenen nöbetlerin daha çok temporal lobtan köken aldığı ve temporal lobektemi sonrası hastaların ¾'ünde nö-betlerin kontrol altına alındığı bildirilmiştir.…”
Section: Discussionunclassified
“…[2,7] Nevertheless, the majority of authors postulate that multiple precipitating factors are involved in the process, or the complete sequence of eating a meal is required to provoke a seizure. [4,5] In our case, the seizures started following chewing, swallowing or drinking. Masticatory movements of the jaw, tongue action, or swallowing may have been the triggering factors.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the unilateral vagus nerve bilaterally modulates the ascending activity at the brain stem level, after going through the tractussolitarius complex. [4] In addition to all these mechanisms, Blauwblomme et al [11] identified overlaps between the gustatory cortex, involving insular, parietal, and frontal regions, and a frontoinsulo-hippocampal epileptogenic network. This epileptogenic network theory may support the mechanism of EE after frontal meningioma resection in our patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation